Craniosynostosis in Growing Children : Pathophysiological Changes and Neurosurgical Problems - Choi, Jung Won (J Korean Neurosurg Soc, 2016)
Craniosynostosis is defined as the premature fusion of one or more cranial sutures resulting in skull deformity. Characteristically, this disorder can cause diverse neurosurgical problems, as well as abnormal skull shape. Intracranial hypertension, hydrocephalus, Chiari malformation and neuropsychological dysfunction are the major neurosurgical concerns in children with craniosynostosis. In this review article, we investigate pathophysiology, characteristics and proper neurosurgical management of these neurosurgical issues, respectively.